Photoelectrochemical detection method of mycotoxins

CN117517422BActive Publication Date: 2026-10-27JIANGXI NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311391932.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2026-10-27
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

但是目前为止,还未见利用Cu2O@ZIF-8用于构建的光电化学传感器用于赭曲霉毒素的相关报道

Benefits of technology

[0034]1)本发明采用Cu2O@ZIF-8来产生光电流信号,将Cu2O包封在ZIF-8材料中,ZIF-8不仅可以保护Cu2O不被光腐蚀,增强其稳定性,而且与Cu2O之间的协同作用也有效促进了载流子的迁移和空穴的产生,从而表现出强的光电流信号响应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117517422B_ABST
    Figure CN117517422B_ABST
Patent Text Reader

Abstract

The application discloses a photoelectrochemical detection method for mycotoxins. The method is to coat ZIF-8 on the surface of Cu2O NPs to synthesize Cu2O@ZIF-8 composite materials, and modify the composite materials on the surface of a GCE electrode to generate a strong photocurrent signal. Meanwhile, a DNA hydrogel constructed by a mycotoxin aptamer can load a large amount of GOx, and after the introduction of target mycotoxins, the structure of the hydrogel is destroyed, the released GOx is used to catalyze glucose to generate gluconic acid, the Cu2O@ZIF-8 is cracked, the photocurrent signal is reduced, and the high-sensitivity and high-selectivity detection of mycotoxins can be realized by measuring the change of the photocurrent signal before and after the change.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for detecting mycotoxins, specifically to a method for detecting mycotoxins using a photoelectrochemical sensor constructed based on encapsulated cuprous oxide metal-organic frameworks (MOFs), belonging to the field of photoelectrochemical bioanalysis. Background Technology

[0002] Ochratoxins are secondary metabolites produced by fungi in the genera *Aspergillus* and *Penicillium*. Ochratoxin A (OTA) is particularly toxic, widely distributed, and poses a significant threat to human health (a Group 2B carcinogen). It is found in common agricultural products such as beans, corn, wheat, wine, and coffee beans. OTA exhibits high thermal and chemical stability, readily accumulating in the human body and causing severe toxic effects.

[0003] In recent years, many analytical methods have been successfully applied to the quantitative analysis of aflatoxin A. Mohammad et al. used ultra-high performance liquid chromatography with fluorescence detection (UHPLC-FLD) to detect the contamination levels of four substances, aflatoxin B1, B2, G1, and G2, in coffee samples. The results showed that the four substances were well separated (Al-Ghouti MA, Alhusaini A, Abu-Dieyeh MH, et al. Determination of aflatoxins in coffee by means of ultra-high performance liquid chromatography-fluorescence detector and fungisolation[J]. International Journal of Environmental Analytical Chemistry, 2022, 102(18):6999-7014.). HPLC has the characteristics of high throughput, high selectivity, and fast separation speed, but it has disadvantages such as long detection time, high detection cost, and inability to rapidly detect large batches of samples, which still have certain limitations in practical applications.

[0004] Herrero et al. first analyzed plant-based beverages using the QuEChERS method, establishing an ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS / MS) method to simultaneously detect 11 mycotoxins in soybean, oat, and rice plant-based beverages (Miro-Abella E, Herrero P, Canela N, et al. Determination of mycotoxins in plant-based beverages using QuEChERS and liquid chromatography-tandem mass spectrometry[J]. Food Chemistry, 2017, 229:366-372.). LC-MS can simultaneously detect multiple mycotoxins with high accuracy and sensitivity, but its complex operation, expensive instruments, and high detection cost limit its application to some extent. Compared with these methods, photoelectrochemical-based biosensor platforms have significant advantages such as low detection limits, high sensitivity, and good specificity, enabling sensitive detection of OTAs. However, to date, there are no reports on the use of Cu2O@ZIF-8 to construct photoelectrochemical sensors for ochratoxin detection. Summary of the Invention

[0005] To overcome the shortcomings and defects of existing technologies, the present invention aims to provide a method for detecting mycotoxins through photoelectrochemical methods. This method uses a Zn metal-organic framework (Cu2O@ZIF-8) composite material encapsulating cuprous oxide to generate a photocurrent signal. Simultaneously, a mycotoxin-target-responsive DNA hydrogel encapsulating glucose oxidase (GOx) oxidizes glucose to produce gluconic acid. Based on the characteristic that gluconic acid can cleave Cu2O@ZIF-8 and reduce its photocurrent signal, a biosensor is constructed to achieve highly sensitive and selective photoelectrochemical detection of mycotoxins.

[0006] To achieve the above technical objectives, the present invention provides a photoelectrochemical detection method for mycotoxins, the method comprising the following steps:

[0007] 1) After dispersing the Cu2O@ZIF-8 nanocomposite in a solvent, it was dropped onto the electrode surface and dried to obtain a composite electrode; the composite electrode was subjected to photoelectric detection to obtain a photocurrent response value I; the Cu2O@ZIF-8 nanocomposite is composed of Cu2O nanoparticles encapsulated by a metal-organic framework ZIF-8.

[0008] 2) The fungal toxin solution was added to the DNA hydrogel containing glucose oxidase for incubation I, followed by incubation II with glucose solution to obtain the reaction solution; the reaction solution was dropped onto the composite electrode for incubation III, and then photoelectric detection was performed to obtain the photocurrent response value II; the DNA hydrogel was obtained by the specific binding reaction of polyacrylamide grafted with DNA strand 1 and polyacrylamide grafted with DNA strand 2 through the fungal toxin aptamer.

[0009] 3) Perform the same steps as step 2) on a series of fungal toxin solutions of different concentrations to obtain a series of photocurrent response values ​​II, and construct a standard curve between the concentration of the fungal toxin solution and the difference between photocurrent response value II and photocurrent response value I.

[0010] 4) Perform the test mycotoxin solution as in step 2) to obtain the corresponding photocurrent response value, and calculate the concentration of the test mycotoxin solution according to the standard curve.

[0011] The key to the photoelectrochemical detection method for mycotoxins in this invention lies in utilizing a Cu2O@ZIF-8 nanocomposite to generate a photoelectric signal. The Cu2O@ZIF-8 nanocomposite consists of Cu2O nanoparticles encapsulated by a metal-organic framework (ZIF-8). The synergistic effect between ZIF-8 and Cu2O nanoparticles effectively promotes carrier migration and hole generation, resulting in a strong photocurrent signal response. The photogenerated carrier mobility is significantly improved compared to Cu2O nanoparticles alone. Furthermore, the encapsulation effect of ZIF-8 overcomes the susceptibility of Cu2O nanoparticles to photocorrosion, greatly improving their stability. In particular, the Cu2O@ZIF-8 nanocomposite can cleave under the action of gluconic acid, causing a decrease in its photoelectric signal. Based on this, this invention constructs a photoelectrochemical sensor for mycotoxins. This invention introduces a DNA sequence into a polyacrylamide chain. This DNA sequence specifically binds to a mycotoxin aptamer, allowing the polyacrylamide chain to be cross-linked to form a DNA hydrogel with a three-dimensional network structure. Simultaneously, GOx is introduced during the cross-linking process, enabling in-situ embedding or encapsulation of GOx within the DNA hydrogel. This DNA hydrogel exhibits aptamer responsiveness; when mycotoxins are present in the environment, they react specifically with the mycotoxin aptamers bound to the DNA hydrogel, leading to DNA hydrogel lysis and the release of GOx. The higher the concentration of GOx in the environment, the greater the degree of DNA hydrogel lysis and the more GOx released, showing a direct proportional relationship. The released GOx catalyzes the oxidation of glucose to gluconic acid, which is then transferred to a Cu2O@ZIF-8 composite material for incubation. This incubation causes ZIF-8 to lyse, resulting in a decrease in its photocurrent signal. This establishes a relationship between mycotoxin concentration and photocurrent signal magnitude, enabling sensitive detection of mycotoxins by measuring the changes in the photocurrent signal.

[0012] As a preferred embodiment, the Cu2O@ZIF-8 nanocomposite is prepared by the following method: Cu2O nanoparticles are dispersed in a solvent, and then a zinc salt solution and a 2-methylimidazole solution are added and stirred to react, thus obtaining the Cu2O@ZIF-8 nanocomposite. By coating the surface of Cu2O NPs with ZIF-8, a Cu2O@ZIF-8 composite material with stronger photocurrent signal and better stability is synthesized.

[0013] As a preferred embodiment, the reaction conditions are: under a protective atmosphere, at a temperature of 45–55°C, for 0.5–1.5 h.

[0014] This invention assembles ZIF-8 in situ on the surface of Cu2O nanoparticles via coordination reaction. Since the Cu2O nanoparticles are rhombic dodecahedrons, consistent with the cavity morphology of ZIF-8, and the size of the Cu2O molecules is highly matched to the cavity diameter of ZIF-8, Cu2O can be successfully encapsulated within ZIF-8. Individual Cu2O nanoparticles exhibit low photogenerated carrier mobility and are susceptible to photocorrosion. ZIF-8 not only protects the Cu2O nanoparticles from photocorrosion and enhances their stability, but also, through synergistic effects with the Cu2O nanoparticles, effectively promotes carrier migration and hole generation, thus exhibiting a strong photocurrent signal response.

[0015] As a preferred embodiment, the molar ratio of Cu2O nanoparticles to zinc salt and 2-methylimidazole is 1:(4-5):(6-7). Within the preferred ratio range, the generated ZIF-8 can completely encapsulate the Cu2O nanoparticles. If the proportion of Cu2O nanoparticles is too high, some Cu2O nanoparticles cannot be encapsulated in situ by ZIF-8, while if the proportion of Cu2O nanoparticles is too low, some ZIF-8 will not act on the Cu2O nanoparticles.

[0016] As a preferred embodiment, the Cu2O nanoparticles are prepared by dissolving copper salt and surfactant in water, and then adding sodium hydroxide solution and hydroxylamine hydrochloride solution to carry out a precipitation reaction.

[0017] As a preferred embodiment, the precipitation reaction is performed under ultrasonic treatment at room temperature for 0.5–1.5 h. Under these preferred reaction conditions, the synthesized Cu₂O is a rhombic dodecahedron with a morphology consistent with ZIF-8, and the size of the Cu₂O molecules closely matches the cavity diameter of ZIF-8, allowing Cu₂O to be successfully encapsulated within ZIF-8.

[0018] As a preferred embodiment, the GOx-encapsulated DNA hydrogel is prepared by the following method: a solution containing acrylamide-modified DNA chain 1 (SA) and acrylamide is mixed with a solution containing acrylamide-modified DNA chain 2 (SB) and acrylamide, followed by the sequential addition of ammonium persulfate, tetramethylethylenediamine, glucose oxidase, and a fungal toxin aptamer, and the reaction is carried out. Tetramethylethylenediamine acts as a promoter for the generation of free radicals from ammonium persulfate, which is beneficial for polymerization reactions at low temperatures. Free radical polymerization allows DNA chain 1 and DNA chain 2 to be uniformly introduced into polyacrylamide, and DNA chain 1 and DNA chain 2 can specifically bind to the fungal toxin aptamer, thereby cross-linking to form a gel. Taking ochratoxin A aptamer as an example, the sequence of acrylamide-modified DNA chain 1 (SA) is: 5'-acrydite-TTT GAT TCA CAG ATG AGT-3'. The sequence of acrylamide-modified DNA chain 2 (SB) is: 5'-acrydite-TTT AGG TGT GAC GGA TGA-3'. The sequence of the ochratoxin A (OTA) aptamer is: 5'-GAT CGG GTG TGG GTG GCG TAAAGG GAG CAT CGG ACA-3'

[0019] As a preferred embodiment, the reaction conditions are: 20–30°C, reaction time 15–25 min. As a preferred embodiment, the incubation conditions are: 20–30°C, incubation time 0.5–1.5 h.

[0020] As a preferred embodiment, the incubation conditions II are: incubation at 20–30°C for 20–40 minutes.

[0021] As a preferred embodiment, the conditions for incubation III are: incubation at 20–30°C for 10–30 minutes.

[0022] The preparation method of Cu2O nanoparticles of the present invention is as follows: 5 mL of CuCl2 solution (0.1 M) and SDS (0.87 g) were added to 69.2 mL of deionized water, and stirred at 32-34 °C until SDS dissolved. The mixture was then ultrasonically dispersed for 5 min. Then, 1.8 mL of NaOH solution (1.0 M) and 24 mL of NH2OH·HCl solution (0.1 M) were added to the mixed solution, and the mixture was ultrasonicated for 1 h. The yellow precipitate was collected by centrifugation and washed twice with a mixture of water and ethanol in a 1:1 volume ratio.

[0023] The preparation method of Cu2O@ZIF-8 of the present invention is as follows: Prepared Cu2O NPs and PVP (1g) are dispersed in 20mL of methanol. After sonication for 5min, 20mL of a methanol solution containing Zn(NO3)2·6H2O (0.7g) and PVP (0.25g) and another equal volume of a methanol solution containing 2-methylimidazole (0.26g) and PVP (0.25g) are added sequentially. The mixture is stirred at 50℃ for 1h under an argon atmosphere. After the reaction is complete, the precipitate is collected by centrifugation, washed three times with methanol solution, and dried in a vacuum oven at 60℃ for 12h to obtain Cu2O@ZIF-8.

[0024] The method for preparing the GOx-loaded DNA hydrogel of the present invention is as follows: 10 μM SA (DNA strand A with acrylamide groups - A) and SB (DNA strand B with acrylamide groups) are prepared separately using a 10 mM Tris-HCl buffer solution containing 200 mM NaCl, 1 mM EDTA, and 4% acrylamide. Solution A, containing 10 μL SA and 10 μL SB, is bubbled under nitrogen for 5 min to remove air. Separately, 0.002 g APS and 2 μL LTEMED are added to 20 μL deionized water to obtain a freshly prepared solution B. 2 μL of solution B is added to solution A, and the mixture is bubbled under nitrogen for 5 min. Then, 10 μL of glucose oxidase (10 μg / mL) is added to the above mixture, and the mixture is bubbled under nitrogen for 5 min. After adding 10 μL of mycotoxin aptamer (10 μM), the mixture is reacted at 25°C for 20 min, during which strands A and B crosslink with the mycotoxin aptamer, ultimately yielding the GOx-loaded DNA hydrogel.

[0025] In the photoelectric detection process of this invention, PEC measurement is performed on a CHI760e electrochemical workstation equipped with a 500W xenon lamp, using a traditional three-electrode system: GCE as the working electrode, platinum wire as the auxiliary electrode, and Ag / AgCl as the reference electrode. The test electrolyte is Na2SO4 (25 mL 0.1 M) solution, and the measured potential is 0.1 V.

[0026] The detection principle of this invention is as follows: A DNA hydrogel is constructed using a mycotoxin aptamer, which serves as part of the DNA hydrogel scaffold. GOx is encapsulated within the DNA hydrogel. When the mycotoxin is present, the mycotoxin aptamer specifically binds to the mycotoxin, causing the DNA hydrogel to rupture. This releases the encapsulated GOx from the hydrogel, catalyzing the production of a large amount of gluconic acid from glucose. The gluconic acid is then transferred to a Cu2O@ZIF-8 composite material for incubation, causing ZIF-8 to lyse and expose Cu2O, resulting in a decrease in its photocurrent signal. Finally, sensitive detection of the mycotoxin can be achieved by measuring the change in the photocurrent signal before and after the reaction.

[0027] This invention proposes a method for detecting fungal toxins using a photoelectrochemical sensor based on a metal-organic framework (MOF) encapsulated with cuprous oxide, comprising the following steps:

[0028] (1) Preparation of GOx-loaded DNA hydrogel: 10 μM SA and SB stock solutions were prepared using a 10 mM Tris-HCl buffer solution containing 200 mM NaCl, 1 mM EDTA, and 4% acrylamide. Solution A, containing 10 μL SA and 10 μL S-B, was then bubbled under nitrogen for 5 min to remove air. Additionally, 0.002 g APS and 2 μL TEMED were added to 20 μL deionized water to obtain freshly prepared solution B. 2 μL of solution B was added to solution A, and the mixture was bubbled under nitrogen for 5 min. Then, 10 μL glucose oxidase (10 μg / mL) was added to the mixture, and the mixture was bubbled under nitrogen for 5 min. Finally, 10 μL of mycotoxin aptamer (10 μM) was added, and the mixture was reacted at 25 °C for 20 min. During this time, chains A and B crosslinked with the mycotoxin aptamer, ultimately yielding a GOx-loaded DNA hydrogel.

[0029] (2) Fabrication of the photoelectrochemical sensor: After polishing, the carbon electrode (GCE) was alternately ultrasonically treated in deionized water and ethanol, and then dried with N2 for later use. Cu2O@ZIF-8 was ultrasonically dispersed in methanol and then modified onto the surface of the GCE. The GCE was then dried in an air stream to obtain Cu2O@ZIF-8 / GCE. Subsequently, the prepared Cu2O@ZIF-8 / GCE composite electrode was subjected to its first PEC measurement.

[0030] To construct the photoelectrochemical sensor, firstly, different concentrations of the target mycotoxin (10 μL) were added to a hydrogel and incubated for 1 h. During this process, the DNA hydrogel ruptured and released glucose oxidase (GOx). Then, 10 μL of 2.0 mM glucose was added to the above solution and incubated for 30 min. During this time, GOx catalyzed the conversion of glucose to gluconic acid. Subsequently, 10 μL of the above reaction solution containing gluconic acid was dropped onto a Cu2O@ZIF-8 / GCE electrode and incubated for 20 min. The Cu2O@ZIF-8 composite material was lysed, gently rinsed with deionized water, and then subjected to a second PEC measurement.

[0031] The specific preparation method of Cu2O nanoparticles of the present invention is as follows: 5 mL of CuCl2 solution (0.1 M) and SDS (0.87 g) were added to 69.2 mL of deionized water, and stirred at 32-34 °C until the SDS dissolved. The mixture was then ultrasonically dispersed for 5 min. Next, 1.8 mL of NaOH solution (1.0 M) and 24 mL of NH2OH·HCl solution (0.1 M) were added to the mixed solution, and the mixture was ultrasonicated for 1 h. The yellow precipitate was collected by centrifugation. Finally, the precipitate was washed twice with a 1:1 mixture of water and ethanol and dispersed in ethanol for later use.

[0032] The specific preparation method of Cu2O@ZIF-8 of the present invention is as follows: The prepared Cu2O NPs and PVP (1g) were dispersed in 20mL of methanol and sonicated for 5min. Then, 20mL of methanol solution containing Zn(NO3)2·6H2O (0.7g) and PVP (0.25g) and another equal volume of methanol solution containing 2-methylimidazole (0.26g) and PVP (0.25g) were added sequentially, and the mixture was stirred at 50℃ for 1h under an argon atmosphere. After the reaction was completed, the precipitate was collected by centrifugation, washed three times with methanol solution, and dried in a vacuum oven at 60℃ for 12h to obtain Cu2O@ZIF-8.

[0033] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:

[0034] 1) This invention uses Cu2O@ZIF-8 to generate photocurrent signals. Cu2O is encapsulated in ZIF-8 material. ZIF-8 can not only protect Cu2O from photocorrosion and enhance its stability, but also the synergistic effect between Cu2O and Cu2O can effectively promote the migration of charge carriers and the generation of holes, thus exhibiting a strong photocurrent signal response.

[0035] 2) This invention employs a signal amplification method using DNA hydrogels. DNA hydrogels possess biocompatibility, sequence designability, and biodegradability. Due to the presence of cross-linked networks, the hydrogel can swell in water and maintain a certain shape and volume, which can encapsulate GOx. When fungal toxins bind to the fungal toxin aptamers on the DNA hydrogel, the hydrogel ruptures, releasing GOx, which catalyzes the conversion of glucose into gluconic acid, thereby destroying ZIF-8.

[0036] 3) The signal-reducing photoelectrochemical sensing strategy for mycotoxin detection constructed in this invention operates within the range of 0.0001–0.05 ng / mL. -1 Within the concentration range, the photocurrent exhibits a good linear relationship with the logarithm of the target concentration, demonstrating advantages such as a wide linear range and low detection limit. Attached Figure Description

[0037] Figure 1The detection principle of OTA by an optochemical sensor based on a metal-organic framework encapsulated with Cu2O and a DNA hydrogel.

[0038] Figure 2 (A) is a scanning electron microscope (SEM) image of Cu2O NPs; (B) is a scanning electron microscope (SEM) image of Cu2O@ZIF-8; (C) is an X-ray energy dispersive spectroscopy (EDS) image of Cu2O@ZIF-8; (D) are powder X-ray energy dispersive spectroscopy (EDS) images of ZIF-8 (black line) and Cu2O@ZIF-8 (red line).

[0039] Figure 3 (A) and (B) are scanning electron microscope images of the Cu2O@ZIF-8 composite material before and after cleavage with gluconic acid; (C) images with different concentrations of target molecules (a: none, b-g: 0.005 ng·mL) in the absence or presence of the target molecule (g: 0.005 ng·mL). -1 0.001 ng·mL -1 0.05 ng / mL -1 0.01 ng·mL -1 and 0.1 ng·mL -1 The UV absorption spectrum of the supernatant of the hydrogel containing Au·NPs under the following conditions; (D) in (a) Cu2O / GCE, (b) Cu2O@ZIF-8 / GCE, and in (c) 100 ng·mL -1 Photocurrent response diagram under target OTA condition.

[0040] Figure 4 (A) represents the relationship between ΔI and OTA concentration, and Figure 4 (B) Linear relationship with the logarithm of OTA concentration; Figure 4 (C) Different concentrations of OTA (ag: 0, 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.05 ng / mL) -1 The photocurrent response of the PEC sensor; Figure 4 (D) Stability testing of PEC biosensors.

[0041] Figure 5 (A) Effect of glucose concentration on signal value; (B) Effect of GOx concentration on signal value; (C) Effect of reaction time of gluconic acid with Cu2O@ZIF-8 composite material on the performance of PEC sensor for detecting OTA. Detailed Implementation

[0042] The technical solution of the present invention will be further described below through specific implementation examples, but these examples should not be used to limit the scope of the present invention.

[0043] To obtain the best performance analysis of this method, several important experimental conditions were optimized, and other operations and conditions are as described in Example 1.

[0044] (1) The effect of glucose concentration on the performance of the PEC sensor for detecting OTA was investigated. Signal values ​​were measured within the concentration range of 0.5–3.0 mM, and the optimal signal value was found at a glucose concentration of 2 mM (e.g., ...). Figure 5 (As shown in A).

[0045] (2) The effect of GOx concentration on the performance of the PEC sensor for OTA detection was investigated in the range of 5–20 μg·mL⁻¹. -1 The signal was measured within a concentration range, and the result was obtained at a GOx concentration of 10 μg·mL⁻¹. -1 When the signal value reaches its optimal value (e.g.) Figure 5 (As shown in B).

[0046] (3) The effect of the gluconic acid pyrolysis time of Cu2O@ZIF-8 composite material on the performance of the PEC sensor for OTA detection was investigated. Taking 100 mg / mL OTA as an example, the signal was measured in the range of 0–40 min. The optimal signal value was found when the pyrolysis time was 20 min (e.g., 100 mg / mL OTA). Figure 5 (As shown in C).

[0047] Example 1

[0048] (1) Add 5 mL of CuCl2 solution (0.1 M) and SDS (0.87 g) to 69.2 mL of deionized water, stir at 33 °C until SDS dissolves, and sonicate for 5 min. Then add NaOH solution (1.8 mL 1.0 M) and NH2OH·HCl solution (24 mL 0.1 M) to the mixed solution, sonicate for 1 h, and centrifuge to collect the yellow precipitate. Finally, wash twice with a 1:1 mixture of water and ethanol, and disperse in ethanol for later use.

[0049] (2) The Cu2O NPs prepared in step (1) and PVP (1g) were dispersed in 20mL of methanol. After sonication for 5min, 20mL of methanol solution containing Zn(NO3)2·6H2O (0.7g) and PVP (0.25g) and another equal volume of methanol solution containing 2-methylimidazole (0.26g) and PVP (0.25g) were added sequentially. The mixture was stirred at 50℃ for 1h under an argon atmosphere. After the reaction was completed, the precipitate was collected by centrifugation, washed three times with methanol solution, and dried in a vacuum oven at 60℃ for 12h to obtain Cu2O@ZIF-8.

[0050] (3) After preparing 10 μM SA and SB stock solutions using a 10 mM Tris-HCl buffer solution containing 200 mM NaCl, 1 mM EDTA, and 4% acrylamide, solution A containing 10 μL SA and 10 μL S-B was bubbled under nitrogen for 5 min to remove air. Meanwhile, 0.002 g APS and 2 μL TEMED were added to 20 μL deionized water to obtain freshly prepared solution B. 2 μL of solution B was added to solution A and bubbled under nitrogen for 5 min. Then, 10 μL glucose oxidase (10 μg / mL) was added to the above mixture and bubbled under nitrogen for 5 min. After adding 10 μL of OTA aptamer (10 μM), the mixture was reacted at 25 °C for 20 min, during which the A and B strands were cross-linked with the OTA aptamer, ultimately yielding a DNA hydrogel loaded with GOx.

[0051] (4) After polishing, the glassy carbon electrode (GCE) was alternately ultrasonically treated in deionized water and ethanol, and then dried with N2 for later use. Cu2O@ZIF-8 was ultrasonically dispersed in methanol and then modified onto the surface of the GCE. It was then dried in an air stream to obtain Cu2O@ZIF-8 / GCE. Subsequently, the prepared Cu2O@ZIF-8 / GCE composite electrode was subjected to its first PEC measurement.

[0052] (5) Different concentrations of target OTA (10 μL) were added to the hydrogel and incubated for 1 h. During this process, the DNA hydrogel ruptured and released glucose oxidase (GOx). Then, 10 μL of 2.0 mM glucose was added to the above solution and incubated for 30 min. During this time, GOx catalyzed the conversion of glucose to gluconic acid. Subsequently, 10 μL of the above reaction solution containing gluconic acid was dropped onto the Cu2O@ZIF-8 / GCE electrode and incubated for 20 min. A 500 W xenon lamp was used as the light source, and a conventional three-electrode system was employed, with GCE as the working electrode, platinum wire as the auxiliary electrode, and Ag / AgCl as the reference electrode. The test electrolyte was Na2SO4 (25 mL 0.1 M) solution, and the measured potential was 0.1 V.

[0053] Because the Cu2O@ZIF-8 composite material is decomposed, the photocurrent response value decreases, and the current response value has a definite relationship with the OTA concentration, thus achieving sensitive detection of OTA; the above detection is performed by replacing the OTA standard solution with the test solution, and the concentration result is obtained through the standard curve.

[0054] Figure 1 The principle of OTA detection using a photoelectrochemical sensor constructed based on a Cu2O-encapsulated metal-organic framework and DNA hydrogel.

[0055] Figure 2 (A) is a scanning electron microscope image of Cu2O NPs. Figure 2(B) is a scanning electron microscope (SEM) image of Cu2O@ZIF-8. The SEM image shows that the Cu2O nanoparticles are rhombic dodecahedrons, consistent with the morphology of ZIF-8. The size of the Cu2O molecules and the cavity diameter of ZIF-8 are very well matched, indicating that Cu2O can be successfully encapsulated within ZIF-8. Individual Cu2O exhibits low photogenerated carrier mobility and is susceptible to photocorrosion. ZIF-8 not only protects Cu2O from photocorrosion and enhances its stability, but the synergistic effect between ZIF-8 and Cu2O effectively promotes carrier migration and hole generation, thus exhibiting a strong photocurrent signal response. Figure 2 (C) shows the X-ray energy dispersive spectroscopy (EDS) of Cu2O@ZIF-8. The EDS indicates that the material contains five elements: C, N, O, Cu, and Zn, confirming the successful synthesis of the Cu2O@ZIF-8 composite material. Figure 2 (D) Powder X-ray energy dispersive spectroscopy (EDS) of ZIF-8 (black line) and Cu2O@ZIF-8 (red line). The PES of ZIF-8 peak positions are basically consistent with those described in the literature, and no diffraction peaks of Cu2O are found, indicating that Cu2O is located in the cavity of ZIF-8 rather than on the surface.

[0056] Figure 3 (A) and (B) are scanning electron microscope images of Cu2O@ZIF-8 composite material before and after pyrolysis by gluconic acid. The comparison shows that the surface of Cu2O@ZIF-8 composite material collapsed significantly after pyrolysis by gluconic acid, exhibiting an irregular shape, indicating that the pyrolysis of the composite material was caused by the detection system. Figure 3 (C) In the absence of (a) or with different concentrations of target molecules (bg: 0.005 ng·mL) -1 0.001 ng·mL -1 0.05 ng / mL -1 0.01 ng·mL -1 and 0.1 ng·mL -1 The ultraviolet absorption spectrum of the supernatant of the hydrogel containing Au·NPs is shown in the figure. It can be concluded from the figure that OTA can destroy the structure of the hydrogel and release the enzyme. Figure 3 (D)(a) Cu2O / GCE, (b) Cu2O@ZIF-8 / GCE, and (c) 100 ng·mL -1 Photocurrent response under target OTA conditions. The figure demonstrates the feasibility of the PEC biosensor based on Cu2O@ZIF-8 composite material and DNA hydrogel.

[0057] Figure 4 The results of the test on the standard sample in Example 1 are shown in (A), where ΔI and OTA concentration are in the range of 0.0001-0.05 ng / mL. -1Relationships within the scope and Figure 4 (B) The linear relationship between ΔI and the logarithm of OTA concentration; Figure 4 (C) Different concentrations of OTA (ag: 0, 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.05 ng / mL) -1 The photocurrent response of the PEC sensor; Figure 4 (D) Stability testing of PEC biosensors.

[0058] The above description is only the preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention shall be covered by the present invention.

Claims

1. A photoelectrochemical detection method for fungal toxins, characterized in that: Includes the following steps: 1) After dispersing Cu2O@ZIF-8 nanocomposite in a solvent, it is dropped onto the electrode surface and dried to obtain a composite electrode; the composite electrode is subjected to photoelectric detection to obtain a photocurrent response value I; the Cu2O@ZIF-8 nanocomposite is composed of Cu2O nanoparticles encapsulated by a metal-organic framework ZIF-8; the Cu2O@ZIF-8 nanocomposite is prepared by the following method: Cu2O nanoparticles are dispersed in a solvent, and then zinc salt solution and 2-methylimidazole solution are added and stirred to react, thus obtaining the Cu2O@ZIF-8 nanocomposite; 2) The fungal toxin solution was added to the DNA hydrogel containing glucose oxidase for incubation I, followed by incubation II with glucose solution to obtain the reaction solution; the reaction solution was dropped onto the composite electrode for incubation III, and then photoelectric detection was performed to obtain the photocurrent response value II; the DNA hydrogel was obtained by the specific binding reaction of polyacrylamide grafted with DNA strand 1 and polyacrylamide grafted with DNA strand 2 through the fungal toxin aptamer. 3) Perform the same operation as step 2) on a series of fungal toxin solutions of different concentrations to obtain a series of photocurrent response values ​​II, and construct a standard curve between the concentration of the fungal toxin solution and the difference between photocurrent response value II and photocurrent response value I. 4) Perform the test mycotoxin solution as in step 2) to obtain the corresponding photocurrent response value, and calculate the concentration of the test mycotoxin solution according to the standard curve.

2. The photoelectrochemical detection method for mycotoxins according to claim 1, characterized in that: The stirring reaction conditions are: under a protective atmosphere, at a temperature of 45~55℃, for 0.5~1.5h.

3. The photoelectrochemical detection method for mycotoxins according to claim 1, characterized in that: The molar ratio of Cu2O nanoparticles to zinc salt and 2-methylimidazole is 1:(4~5):(6~7).

4. The photoelectrochemical detection method for mycotoxins according to claim 1, characterized in that: The Cu2O nanoparticles were prepared by dissolving copper salt and surfactant in water, and then adding sodium hydroxide solution and hydroxylamine hydrochloride solution to carry out a precipitation reaction.

5. The photoelectrochemical detection method for mycotoxins according to claim 4, characterized in that: The precipitation reaction was carried out under ultrasonic treatment at room temperature for 0.5 to 1.5 hours.

6. The photoelectrochemical detection method for mycotoxins according to claim 1, characterized in that: The DNA hydrogel containing glucose oxidase was prepared by the following method: a solution containing acrylamide-modified DNA strand 1 and acrylamide was mixed with a solution containing acrylamide-modified DNA strand 2 and acrylamide, and then ammonium persulfate, tetramethylethylenediamine, glucose oxidase and fungal toxin aptamer were added in sequence to carry out the reaction. The fungal toxin aptamer can specifically bind to DNA strand 1 and DNA strand 2.

7. The photoelectrochemical detection method for mycotoxins according to claim 6, characterized in that: In the preparation of the DNA hydrogel containing glucose oxidase, the reaction conditions are: 20~30℃, reaction time 15~25min.

8. The photoelectrochemical detection method for mycotoxins according to claim 1, characterized in that: The conditions for incubation I are: incubation at 20~30℃ for 0.5~1.5h; The conditions for incubation II are: incubation at 20~30℃ for 20~40 min; The conditions for incubation III are: incubation at 20~30℃ for 10~30 minutes.

Citation Information

Patent Citations

  • Preparation method of photoelectrochemical NSE sensor based on controlled release of ZIF-8 shielding shell layer

    CN114674896A